2011
DOI: 10.1007/s00464-010-1566-0
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic colonography in preoperative evaluation of colorectal tumors: a prospective study

Abstract: BackgroundThis study aimed to assess the usefulness of computed tomographic colonography (CTC) in preoperative evaluation of colorectal tumors and the entire bowel including endoscopically inaccessible regions.MethodsColonoscopy and CTC were performed for 49 patients. The tumor and the entire colon were assessed, and the results were compared with colonoscopy. The extraluminal findings of CTC were compared with contrast-enhanced computed tomography (CT) of the abdomen and the pelvis in 33 patients. All these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…A recent study including 286 CRC cases after failed colonoscopy showed CTC negative predictive values (NPVs) of 100% and 97% for synchronous cancer and advanced neoplasia, respectively, in a preoperative setting [ 58 ]. This is in line with a previous systematic review, showing equivalent sensitivity of colonoscopy and CTC for established cancer [ 22 ], and in line with findings from similar cohort studies [ 44 , 59 63 ].…”
Section: Ct Colonography Following Incomplete Colonoscopysupporting
confidence: 92%
“…A recent study including 286 CRC cases after failed colonoscopy showed CTC negative predictive values (NPVs) of 100% and 97% for synchronous cancer and advanced neoplasia, respectively, in a preoperative setting [ 58 ]. This is in line with a previous systematic review, showing equivalent sensitivity of colonoscopy and CTC for established cancer [ 22 ], and in line with findings from similar cohort studies [ 44 , 59 63 ].…”
Section: Ct Colonography Following Incomplete Colonoscopysupporting
confidence: 92%
“…CTC is an established method to screen for polyps and colorectal cancer . OC is regarded as the standard procedure for the detection of colorectal lesions and for the preoperative evaluation of patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Optical colonoscopy (OC) is used for screening and as part of the preoperative evaluation of patients with colorectal cancer . CT colonography (CTC) is a post‐processing imaging technique that can be used to screen for colorectal cancer and polyps and to preoperatively evaluate colorectal tumors . Previous reports have shown that the sensitivity of CTC compares favorably with that of OC for the detection of colorectal lesions .…”
Section: Introductionmentioning
confidence: 99%
“…It can also evaluate extraluminal pathology, which might contribute to a patient's symptom. [ 2 6 7 16 17 ]…”
Section: Discussionmentioning
confidence: 99%